A simulation of factors impeding water quality trading - Smith, Craig M.; Peterson, Jeffrey M.; Leatherman, John C.; Williams, Jeffery R. (My University, 2013)
While there is substantial evidence that nonpoint sources have lower nutrient reduction costs than point sources, experience with water quality trading (WQT) reveals a common theme: little or no trading activity. The success of WQT seems, in part, to depend on the structure of the market created to bring buyers and sellers together to transact exchanges. To examine the ways that various market imperfections may affect the performance of a WQT market, a model is constructed which simulates a hypothetical point-nonpoint market. This paper focuses on answering the following question: How can WQT programs be designed in ways that take into account factors that result in non-optimal contracting and what are the implications (if there are any) for determining trading ratios? Here, we find that apart from any implications for environmental risk or political-economic factors, there is an economic welfare justification for high trading ratios in certain situations with limited trading information and/or other barriers to trade. Limited information and other barriers to trade which inhibit the optimal contracting of trades introduces a random element to market participation, creating a risk that high-cost sellers (low-value buyers) will transact to displace low-cost sellers (high-value buyers) who could have traded for greater gain.
Keywords: Water quality trading